Improving Students’ Tenses Mastery through Tenses Symbol Technique (TST) in Class X4 at SMA Negeri 1 Pekanbaru - Khairunnisah Khairunnisah (UIR Press, 2018)
Student’s Tenses mastery is an important competence to support the major English skills, listening, speaking, reading, and writing. Beside, the tenses mastery is also important to have another grammar materials that need Tenses mastery as the basic knowledge. However, in reality, students’ tenses mastery is very minimal that they are not able to call out the names of the tenses, mention the formulas, let alone to understand meaning and the usage in sentences. To solve this problem the resercher has created a teaching technique, namely, Tenses Symbols Technique (TST) that covers four steps of tenses mastery: memorizing tenses names, formulating tenses patterns, understanding tenses meanings, dan applying in context. Clasroom Action Research is the research method applied in this research because the aim of this research merely to solve the problem the researcher has in her own class. From the two cycles of Classroom Action Research that consists of planning, acting, observing, and reflecting, and from data analyzing , it was proven that Tenses Symbols Tecnique (TST) could improve the students’ tenses mastery as 81% in cycle 1 and 95% in cycle 2 because the application of symbols in this technique could simplify of the process of decoding the meaning of each tenses. So, the result of this research is TST could improve students’ tenses mastery.